Microbial ureases: significance, regulation, and molecular characterization. - Mobley, H L (1989)
Microbial ureases hydrolyze urea to ammonia and carbon dioxide. Urease activity of an infectious microorganism can contribute to the development of urinary stones, pyelonephritis, gastric ulceration, and other diseases. In contrast to these harmful effects, urease activity of ruminal and gastrointestinal microorganisms can benefit both the microbe and host by recycling (thereby conserving) urea nitrogen. Microbial ureases also play an important role in utilization of environmental nitrogenous compounds and urea-based fertilizers. Urease is a high-molecular-weight, multimeric, nickel-containing enzyme. Its cytoplasmic location requires that urea enter the cell for utilization, and in some species energy-dependent urea uptake systems have been detected. Eucaryotic microorganisms possess a homopolymeric urease, analogous to the well-studied plant enzyme composed of six identical subunits. Gram-positive bacteria may also possess homopolymeric ureases, but the evidence for this is not conclusive. In contrast, ureases from gram-negative bacteria studied thus far clearly possess three distinct subunits with Mrs of 65,000 to 73,000 (alpha), 10,000 to 12,000 (beta), and 8,000 to 10,000 (gamma). Tightly bound nickel is present in all ureases and appears to participate in catalysis. Urease genes have been cloned from several species, and nickel-containing recombinant ureases have been characterized. Three structural genes are transcribed on a single messenger ribonucleic acid and translated in the order gamma, beta, and then alpha. In addition to these genes, several other peptides are encoded in the urease operon of some species. The roles for these other genes are not firmly established, but may involve regulation, urea transport, nickel transport, or nickel processing.